(untitled) (Research, Society and Development, 2021)
Can the time it takes a student to complete a test influence his / her performance? To answer this question, the logistic regression model was considered. In its development, evaluation was considered as a way of quantifying the performance of a student reflecting his degree of knowledge in a given content. For this we use records of the initial and final moments when developing an evaluation. The records of time spent were obtained from five different undergraduate classes, with subjects taught by the same teacher, with the same theoretical content, at the same university. The results confirm statistically that each additional minute that the student remains taking the test, implies in greater chances of obtaining good performance, as well as differences of performance between the feminine and masculine genders, although not statistically different, demonstrating that feminine students have greater chances of reaching the average. The model also confirms, according to the odds ratios that during the evaluations the students’ performance decreases, having the best score in the first test. Through the references consulted, we understand that the difference in the grades of each student is influenced by several factors, the result of their own experiences.